(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2021)
The accrescent wings of the sámaras of Stigmaphyllon nudiflorum, a Malpighiaceae liana endemic to the dry forest of the Guayas province, on the coast of Ecuador, are reported here for the first time for the species and for the genus. In addition, based on a previous study of the age and biogeographic history of this genus coupled to the origin of the soils where S. nudiflorum inhabits, a hypothesis is presented here about the evolutionary origin of this and other related species endemic to the southeast area of the Chongón-Colonche mountain range, in western Ecuador.